METHODS OF MANAGEMENT COMPETENCE FORMING OF FUTURE ECONOMISTS - Alla Grusheva (Науковий вісник Інституту професійно-технічної освіти НАПН України: Професійна педагогіка, 2018)
The introduction of a competence approach in the system of professional training of specialists raises the need to study the content and structure of various competencies. According to the results of the study, it is revealed that the majority of students dream of managing positions of different managerial level. To do this, they need to master new knowledge in economics and management, learn how to use them in practice, constantly improve them. This issue does not lose relevance over time, as the task of professional training of specialists in various specialties and the conditions for their implementation change dynamically and regularly. The effectiveness of the formation of managerial competence depends on the definition of its essence and the content of training in discipline, the choice of pedagogical technologies, the development of a rational model of the process of forming and determining the criteria and levels of its formation. According to the results of the ascertaining stage of the pedagogical experiment, it is established that the essence of managerial competence is manifested in its multidimensionality and focus of the activity of the manager on the management object, taking into account its specificity and the nature of development in the socially cohesive environment; in a complex of knowledge, forms and methods of management; display readiness and ability to effectively design and implement management activities; in the integral characteristic of managers.